2006
DOI: 10.1038/sj.eye.6702375
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the darkroom prone provocative test in family members of primary angle closure glaucoma patients

Abstract: Purpose To compare ocular biometric parameters with darkroom prone provocative test (DRPPT) in family members of primary angle closure glaucoma (PACG) patients. Methods One hundred and forty-nine family members of 46 PACG patients underwent ocular examination included slit lamp biomicroscopy, gonioscopy, fundus examination using þ 90 D lens, Goldmann applanation tonometry, darkroom prone provocative test, perimetry on Humphrey's field analyzer II and optic disc evaluation using HRT II. Ultrasonic ocular biomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…All measures were made on the left eye using a Perkins tonometer (Mk2; Haag-Streit, Essex, UK) by a certified ophthalmologic technician. The Perkins tonometer is a handheld applanation tonometer with a spring-counterweight to compensate for gravity, so IOP can be measured in any posture (9,31,36). The root mean square difference between the Perkins and the gold standard Goldmann applanation tonometer is 1.4 mmHg in the seated position (13) with a potential negative bias of 1 mmHg in the seated position (45) and 1.8 mmHg in the supine position (2).…”
Section: Subjectsmentioning
confidence: 99%
“…All measures were made on the left eye using a Perkins tonometer (Mk2; Haag-Streit, Essex, UK) by a certified ophthalmologic technician. The Perkins tonometer is a handheld applanation tonometer with a spring-counterweight to compensate for gravity, so IOP can be measured in any posture (9,31,36). The root mean square difference between the Perkins and the gold standard Goldmann applanation tonometer is 1.4 mmHg in the seated position (13) with a potential negative bias of 1 mmHg in the seated position (45) and 1.8 mmHg in the supine position (2).…”
Section: Subjectsmentioning
confidence: 99%
“…Dynamic gonioscopy was used to determine whether it was a peripheral anterior synechiae or an appositional attachment. 15 When a convex iris prevented observation of the angle, the patient was requested to look in the direction of the mirror, thereby bringing the angle into view. If the posterior pigmented meshwork could not be seen, corneal indentation was performed with the gonioprism.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported varying lens thickness from 4 to 6 mm. [21][22][23] Assuming an anterior chamber depth of 2.0-3.5 mm, a phaco probe-endothelium distance of 6-7 mm was appropriate assuming in-the-bag phacoemulsification. The 0.9-mm straight phaco tip was used with the bevel facing downward.…”
Section: Methodsmentioning
confidence: 99%